Galicja w muzycznym świecie XIX wieku – widziana z Lipska - Loos, Helmut (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2023)
Music journals give a picture of music history that is always self-referential from the editor’s point of view. This source criticism is part of the evaluation of reports on musical life, as they had great charisma, especially from Leipzig. Serious music as the art religion of modernity received their attention; it was seen as proof of the supremacy of German music and a measure of evolutionary progress in a society. The resulting “master narratives” have long since given way to postmodern enlightenment and are increasingly making way for a realistic portrayal of music history. The expansion and reach of bourgeois musical culture in the 19th century up to the Second World War can be easily traced with the help of Leipzig music journals. Both the number of reports on various European cities and their content provide information about the new, bourgeois musical culture and its pan-European tradition, which had already influenced the music of the nobility and the churches for centuries. From a broader panorama, the cities of Lviv and Cracow are examined a little more closely.